Fazer é pensar, pensar é fazer: o trabalho e os artefatos na Fábrica Zeferino, Novo Hamburgo, RS - Tessari, Valéria Faria dos Santos (2014)
The research I have documented through this text aims at investigating on how the work and artifacts are made at the Zeferino factory, Novo Hamburgo, Rio Grande do Sul, Brasil. Thus, I have explored the ways in which both the modelers and the designer work in this company build their practices in the midst of clashes and tensions. For this, I follow a journey that presents the brand and Zeferino factory, as well as the interlocutors who participated in the study. Likewise, I present artifacts and the particular ways of doing this microcosm to, finally, discuss the struggles through which the work and the artifacts are made there. The procedures conducted for the preparation of this qualitative research were exploratory empirical experiences and narratives interviews on the model of Oral History. I took the narratives of the model development process in order to explore the moments of these conflicts, to interpret the meanings attributed by the interlocutors to these tensions and conflicts. So I intend to set up an image from the development process as well as from the interlocutors which enables individuals to realize their unique work modes, their activities and knowledge, showing the inhomogeneity of the ways of production of artifacts.